The ancient magus' bride. Volume 9 - Yamazaki, Kore (Ancient Magus' Bride, 2018)
A Deal with the Devil. Elias hoped to break the deadly draconic curse that weighs upon Chise-but his methods have created a rift between them. Now Chise prepares to make a gamble of her own: What could she possibly hope to gain from a bargain with Cartaphilus? It is a time of curses cast and forks in the road. Will the paths of master and apprentice soon diverge...?